Pengaruh Pemberian Terapi Komplementer Sujok Terhadap Intensitas Nyeri Sendi Osteoartritis Pada Lansia di Sleman - Lestari, Lestari; Primasari, Nessy Anggun; Widiyanti, Erika Nur (Journal of Nursing Invention, 2025)
Background: Osteoarthritis patients often experience dull or intermittent pain of unpredictable intensity that is initially related to activity and then becomes more constant over time, which is one of the most common chronic conditions and can be disabling. Sujok therapy is effective in reducing pain, especially osteoarthritis. Objective: To determine the effect of providing complementary sujok therapy on the intensity of osteoarthritis joint pain in the elderly at Posyandu Panggungan, Trihanggo, Gamping, Sleman. Method: This research is a quasi-experimental research with a pre-experimental design approach of the One-Group Pre test – Post test Design type. The sampling technique was purposive sampling, totaling 48 people. The researchinstrument used a questionnaire NRS. The data analysis technique uses the Wilcoxon signed ranks test. Results: The intensity of osteoarthritis joint pain in the elderly before being given complementary Sujok therapy was in the majority category of severe pain as many as 28 people (58.3%). The intensity of osteoarthritis joint pain in the elderly after being given complementary Sujok therapy was mostly in the moderate pain category, 32 people (66.7%). There was a decrease in the intensity of osteoarthritis joint pain after being given complementary sujok therapy. The calculated Z_value was -5.099 and the significant value was 0.000 (p<5%). There is an effect of providing complementary sujok therapy on the intensity of osteoarthritis joint pain in the elderly at Posyandu Panggungan, Trihanggo, Gamping, Sleman. Conclusion: Sujok complementary therapy is a holistic therapy method that can be used as a reference for healing joint pain. This has great potential for health workers as an independent alternative